Biopolymer‐Supported Ionic‐Liquid‐Phase Ruthenium Catalysts for Olefin Metathesis. Issue 4 (11th March 2014) - Clousier, Nathalie; Filippi, Alexandra; Borré, Etienne; Guibal, Eric; Crévisy, Christophe; Caijo, Fréderic; Mauduit, Marc; Dez, Isabelle; Gaumont, Annie‐Claude
Abstract Original ruthenium supported ionic liquid phase (SILP) catalysts based on alginates as supports were developed for olefin metathesis reactions. The marine biopolymer, which fulfills most of the requisite properties for a support such as widespread abundance, insolubility in the majority of organic solvents, a high affinity for ionic liquids, high chemical stability, biodegradability, low cost, and easy processing, was impregnated by [bmim][PF6] containing an ionically tagged ruthenium catalyst. These biosourced catalysts show promising performances in ring‐closing metathesis (RCM) and cross‐metathesis (CM) reactions, with a high level of recyclability and reusability combined with a good reactivity.